A new nomenclature for classifying psychotropic drugs. (24th May 2017) - Caraci, Filippo; Enna, Sam J.; Zohar, Joseph; Racagni, Giorgio; Zalsman, Gil; van den Brink, Wim; Kasper, Siegfried; Koob, George F.; Pariante, Carmine M.; Piazza, Pier Vincenzo; Yamada, Kiyofumi; Spedding, Michael; et al.
Abstract: The Neuroscience‐based Nomenclature (NbN) for psychotropic drugs was developed as an alternative to the current Anatomical Therapeutic Chemical (ATC) indication‐based classification in order to provide more precise designations for this drug class. The ATC nomenclature for psychotherapeutics is limited in that it fails to specify either pharmacological domains or mechanism of action and also does not describe all the potential uses of a particular agent. The disconnect between the drug classification and its clinical use is not very useful for scientific purposes and is confusing for patients and caregivers, often leading to a misunderstanding of the intended effects of the prescribed medication and, most importantly, to low treatment adherence. The NbN classifies psychopharmacological agents on the basis of contemporary scientific information on their pharmacology and mechanisms of action so as to provide physicians clear alternatives when selecting or altering therapeutic regimens. The classification of each psychotropic drug includes four additional dimensions: approved indications; efficacy and side effects; practical note; neurobiology. By emphasizing the pharmacology and the molecular mechanism of action, NbN provides a vehicle for clinicians and basic scientists to improve the understanding and clinical use of this important drug class.